The Role of 1 and 9 wt.% Zn in Precipitation Hardening of AA319 Aluminium - Sofyan, Bondan Tiara; Susanti, Sari; Yusfranto, Ridwan R. (Makara Journal of Technology, 2008)
The Role of 1 and 9 wt.% Zn in Precipitation Hardening of AA319 Aluminium. Aluminium alloys are widely used for automotive application due to its low density and high corrosion resistance. For economic reason, casting of automotive products always uses aluminium scrap as charging materials that may result in fluctuation of content of alloying element, such as Zn. This research studies the role of Zn in precipitation hardening of AA319 aluminium alloys. Hardness and tensile testing were conducted to study the mechanical properties of the alloys, while ageing response was followed by hardness measurements. Evolution of microstructures was observed by using optical microscope and SEM (scanning electron microscope) equipped with EDS (energy dispersive spectroscopy). Distribution of solute elements was detected by x-ray mapping and formation of nanoprecipitates was observed by using TEM (transmission electron microscope). Research results showed that addition of 1 and 9 wt. % Zn on AA310 alloys increases strength and hardness. Morphology transformation of Al-Fe-Mn-Si phase from chinese script into needle shape was detected, and may be due to dissolution of Zn in aluminium matrix that change the interfacial stress between the matrix and interdendritic phases. Addition of Zn also increased response of alloys to natural ageing but no significant change was detected for artificial ageing at 200 oC. Age hardening was contributed by the formation of θ’ (Al2Cu) nanoprecipitates. Zn was segregated on the periphery of Al2Cu phase.